A Combination of Podophyllotoxin and Rutin Alleviates Radiation-Induced Pneumonitis and Fibrosis through Modulation of Lung Inflammation in Mice - Verma, Savita; Kalita, Bhargab; Bajaj, Sania; Prakash, Hridayesh; Singh, Ajay Kumar; Gupta, Manju Lata (Frontiers in Immunology, 2017)
Pneumonitis and pulmonary fibrosis are predominant consequences of radiation exposure, whether planned or accidental. The present study, demonstrates radioprotective potential of a formulation, prepared by combining podophyllotoxin and rutin (G-003M), in mice exposed to 11 Gy thoracic gamma radiation (TGR). Treated mice were observed for survival and other symptomatic features. Formation of reactive oxygen species (ROS)/nitric oxide (NO) was measured in bronchoalveolar lavage cells. DNA damage and cell death were assessed in alveolar cells by terminal deoxynucleotidyl transferase dUTP nick-end labeling assay. Total protein (TP), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP) were measured in bronchoalveolar lavage fluid (BALF)/serum of mice to assess lung vascular permeability. Interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), transforming growth factor-β1 (TGF-β1), cluster of differentiation 45, inducible nitric oxide synthase (iNOS), and nitrotyrosine were also estimated in lungs/BALF of differentially treated mice. Our observations revealed 100% survival in G-003M-pretreated mice against 66.50% in 11 Gy TGR exposed. Other symptoms like reduction in graying of hair, weight loss, and breathing rate were also observed in pretreated groups. Significant decline in ROS/NO and cell death in formulation pretreated mice were also observed. Decreased level of TP, LDH, and ALP in BALF/serum samples revealed G-003M-induced inhibition in lung permeability. Level of IL-6, TNF-α, and TGF-β1 in the lungs of these mice was found corresponding to control group at 8 weeks posttreatment. On the contrary, these cytokines raised significantly in 11 Gy TGR-exposed mice. Lung pneumonitis and fibrosis were found significantly countered in these mice. The observations revealed that G-003M could regulate immune system by curtailing radiation-induced oxidative and inflammatory stress, which has helped in minimizing radiation-inflicted pneumonitis and fibrosis.